DETERMINAN INKLUSI KEUANGAN DI INDONESIA (GLOBAL FINDEX 2014) - Nugroho, Ari; Purwanti, Evi Yulia (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2018)
Financial inclusion has been a trend since post 2008 crisis especially derived from the effects of the crisis towards the class in the bottom of the pyramid. Financial inclusion rate in Indonesia, if seen from three main indicators, is still low. Indonesians who have an account in financial institutions is at 35,95 percent and those who save is at 25,56 percent. Meanwhile, Indonesians who borrow in formal financial institutions are only at 13,3 percent. This study aims to examine individual characteristics in influencing three main indicators of financial inclusion, the ownership of the account, saving, and borrowing from formal financial institution in Indonesia. The data used is the micro-level data with 1000 respondents of the Indonesian population obtained from Global Findex 2014 issued by the World Bank. In accordance with the objectives of this study, the method used is the logit regression model.The results of the research shows that individual characteristics such as income level, education level, and age significantly affect ownership and savings accounts in formal financial institutions. While gender has no significant effect. In the third indicator which is the borrowing from formal financial institutions, only the poorest income quintile and age has a significant effect.